The story of music - Ingman, Nicholas; Brett, Bernard (New York : Taplinger Pub. Co., 1976)
A history of music intertwined with the lives and music of great musicians.
Includes index.
Keywords: Music -- History and criticism -- Juvenile literature; Music -- History and criticism; Composers; Musicians